Entrepreneurial Leadership and Innovation: A Systematic Literature Review and Future Research Agenda - Benni Aziz; Yunia Wardi; Susi Evanita; Hendrik Heri Sandi (Publikasi Indonesia, 2026)
This research aims to systematically review the relationship between entrepreneurial leadership and innovation, focusing on key mechanisms and emerging research trends. A Systematic Literature Review (SLR) approach was applied following PRISMA 2020 guidelines. Relevant articles published between 2019 and 2025 were collected from major databases, including Scopus, Web of Science, and ScienceDirect. After a rigorous screening process, 32 studies were selected for analysis. The findings reveal that entrepreneurial leadership significantly enhances innovation outcomes, including innovation performance, innovative behavior, and organizational innovation capability. The relationship is often mediated by psychological factors such as creativity, work engagement, and psychological empowerment, as well as knowledge-based mechanisms including knowledge sharing and organizational learning. In addition, organizational context and digital factors, such as digital capability and artificial intelligence readiness, play an important role in strengthening innovation. This study contributes by synthesizing current literature, identifying research gaps, and proposing directions for future research on entrepreneurial leadership and innovation.